Entamoeba histolytica Up-Regulates MicroRNA-643 to Promote Apoptosis by Targeting XIAP in Human Epithelial Colon Cells - López-Rosas, Itzel; López-Camarillo, César; Salinas-Vera, Yarely M.; Hernández-de la Cruz, Olga N.; Palma-Flores, Carlos; Chávez-Munguía, Bibiana; Resendis-Antonio, Osbaldo; Guillen, Nancy; Pérez-Plasencia, Carlos; Álvarez-Sánchez, María Elizbeth; Ramírez-Moreno, Esther; Marchat, Laurence A. (Frontiers in Cellular and Infection Microbiology, 2019)
MicroRNAs (miRNAs) are evolutionary conserved small non-coding RNAs that function as negative regulators of gene expression. Recent evidence suggested that host miRNAs are involved in the outcome of infectious diseases, but its role in amoebiasis is largely unknown. Here, we reported an unexplored role for miRNAs of human epithelial colon cells during apoptosis induced by Entamoeba histolytica. We show for the first time that human SW-480 colon cells change their miRNAs expression profile in response to parasite exposure. Our data showed that virulent E. histolytica trophozoites induced apoptosis of SW-480 colon cells after 45 min interaction, which was associated to caspases-3 and -9 activation. Comprehensive profiling of 667 miRNAs using Taqman Low-Density Arrays showed that 6 and 15 miRNAs were significantly (FC>1.5; p<0.05) modulated after 45 min and 75 min interaction of SW-480 cells with virulent parasites, respectively. Remarkably, no significant changes in the 6-miRNAs signature (45 min) were found when SW-480 cells were exposed to spent media and non-virulent Entamoeba dispar trophozoites. Exhaustive bioinformatic analysis revealed an intricate miRNAs-mRNAs coregulation network in which the anti-apoptotic XIAP, API5, BCL2 and AKT1 genes were the major common targets of the deregulated miRNAs at 45 min. Of these, we focused in the study of functional relationships between miR-643, upregulated at 45 min interaction, and its predicted target X-linked inhibitor of apoptosis protein (XIAP). Interestingly, interplay of amoeba with SW-480 cells resulted in downregulation of XIAP protein levels consistent with apoptosis activation. More importantly, loss of function studies using antagomiRs showed that forced inhibition of miR-643 leads to restoration of XIAP expression and suppression of apoptosis and caspases -3 and -9 activation after 45 min interaction of trophozoites with SW-480 cells. Congruently, mechanistic studies using luciferase reporter assays confirmed that miR-643 exerts a postranscripcional negative regulation of XIAP by targeting its 3´-UTR indicating that it’s a downstream effector. In summary, we provide novel lines of evidence suggesting that early-branched eukaryote E. histolytica may promote apoptosis of human colon cells by modulating, in part, the host miRNome which highlight an unexpected role for miRNA-643/XIAP axis in the host cellular response to parasites infection.